EDUCATION ON CASH PLANNING AND RECORDING FOR MSMES IN KALI TENGAH VILLAGE, TENGAH TANI SUBDISTRICT, CIREBON REGENCY - Fujianti, Lailah; Kariyani, Etika; Herninta, Tiwi; Indupurnahayu, Indupurnahayu; Purwanti, Ari (LPPM Univ. Ibn Khaldun Bogor, 2024)
The purpose of this service is to help solve MSME problems related to planning and recording business finances / cash. The service in Kali Tengah Village, Tengah Tani District, Cirebon Regency was carried out on Saturday, July 15, 2023. The service was carried out in the form of education to MSMEs, which was attended by 30 actors consisting of batik, processed food, trade and confectionery MSMEs. The results of the service evaluation showed an increase in knowledge in planning and recording cash before and after education.